Multiscale spatial contexts and neighbourhood effects - Petrović, Ana (A+BE | Architecture and the Built Environment, 2020)
This thesis has developed alternative methods of operationalising neighbourhoods at multiple spatial scales and used them to advance our understanding of spatial inequalities and neighbourhood effects. The underlying problem that motivated this thesis is that many empirical studies use predefined administrative units, and this does not often align with the underlying theory or geography. Despite the extensive literature on neighbourhood effects and, more generally, on sociospatial inequalities, spatial scale remains an under-analysed concept. As a response to this research gap, this thesis takes a multiscale approach to both theory and empirical analysis of neighbourhood effects, highlighting the multitude of spatial processes that may affect individual outcomes of people. To operationalise this, we created bespoke areas (centred around each location) at a range of one hundred scales representing people’s residential contexts, primarily in the Netherlands but also in multiple European capitals. Using microgeographic data and a large number of scales combined with small distance increments revealed subtle changes in sociodemographic characteristics across space. In doing so, we provided new insights into ethnic segregation, potential exposures to poverty, and neighbourhood effects on income, all in light of the fundamental issue of spatial scale: The analyses of sociospatial inequalities are substantially affected by the scale used to operationalise spatial context, and this varies within and between cities and urban regions. The aim of this thesis was therefore not to find a single, ‘true’ scale of neighbourhood, but to acknowledge, operationalise, and better understand the multiplicity of spatial scales.